PENGARUH DISIPLIN KERJA, KESELAMATAN DAN KESEHATAN KERJA, SERTA LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN BAGIAN PRODUKSI PT.BARLOW TYRIE INDONESIA - Muhammad Sudwiyatmoko; Rodhiyah Rodhiyah; Sendhang Nurseto (Universitas Diponegoro, 2014)
The development of a dynamic business world and followed with the level of competition to encourage businesses to increase their productivity. To improve employee productivity, good work discipline required that supported also by maintaining awareness of safety and health at work. In addition, the ideal work environment needed to create the convenience of employees during work. All these aspects must be mutually supportive to achieve the objectives of the company. This research method is explanatory, with the technique of collecting data through interviews with questionnaires, observation, and study of literature. Proportionate random sampling technique is used with a sample of 64 people. The analysis technique used is qualitative and quantitative. Results and discussion showed higher labor discipline, the higher the productivity of employees, the better the health and safety of employees, the higher productivity, and better working conditions, the higher the productivity of employees. Categorization of work discipline is high, but quite a lot who are in the low category. Employee safety and health is good, but quite a lot of that is in the low category. Work environment the company is in excellent condition, although still quite a lot that assess the condition is not good. Good levels of employee productivity, but there are many employees who have low productivity.